2015
DOI: 10.1177/0956797615595037
|View full text |Cite
|
Sign up to set email alerts
|

Confidence Leak in Perceptual Decision Making

Abstract: We live in a continuous environment in which the visual scene changes on a slow timescale. It has been shown that, to exploit such environmental stability, the brain creates a “continuity field” such that objects seen seconds ago influence the perception of current objects. What is unknown is whether a similar mechanism exists at the level of our metacognitive representations. In three experiments we demonstrate a robust inter-task “confidence leak” that cannot be explained by response priming or attentional f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
155
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(177 citation statements)
references
References 34 publications
22
155
0
Order By: Relevance
“…In contrast to the linear positive correlation observed for cardiac acceleration, pupil dilation covaried biphasically with subjective confidence, reversing from positive to negative during subjective ratings (see Figure 3—figure supplement 1A). This result may partially account for recent findings that distinct stimulus-related and post-decisional computations underlie the representation of confidence (Lebreton et al, 2015; Rahnev et al, 2015), and corroborates the previously reported link between pupil variability and confidence for an auditory discrimination task (Lempert et al, 2015). Furthermore, although interoceptive (i.e., cardiac) sensitivity and meta-cognition for memory have previously been related to one another (Garfinkel et al, 2013), our study is the first to show that confidence reports for perception correlate positively with cardiac acceleration.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast to the linear positive correlation observed for cardiac acceleration, pupil dilation covaried biphasically with subjective confidence, reversing from positive to negative during subjective ratings (see Figure 3—figure supplement 1A). This result may partially account for recent findings that distinct stimulus-related and post-decisional computations underlie the representation of confidence (Lebreton et al, 2015; Rahnev et al, 2015), and corroborates the previously reported link between pupil variability and confidence for an auditory discrimination task (Lempert et al, 2015). Furthermore, although interoceptive (i.e., cardiac) sensitivity and meta-cognition for memory have previously been related to one another (Garfinkel et al, 2013), our study is the first to show that confidence reports for perception correlate positively with cardiac acceleration.…”
Section: Discussionsupporting
confidence: 90%
“…This last explanation also fits with the monkey data discussed above (33). In partial support of this last possibility, we previously suggested a role for aPFC in decreasing the amount to which confidence on a previous trial biases the confidence rating on a current trial, a phenomenon dubbed "confidence leak" (37). Such confidence leak is likely beneficial in most everyday tasks but is suboptimal in laboratory tasks in which successive trials are independent and the previous stimulus should therefore be ignored during the current decision.…”
Section: Discussionsupporting
confidence: 82%
“…Because regions of the DAN have been implicated as substrates of attentional control underlying modulations of posterior alpha oscillations (Capotosto, Babiloni, Romani, & Corbetta, 2009; Marshall, O’Shea, Jensen, & Bergmann, 2015; Mathewson et al, 2014), it is possible that the relationship between alpha power and confidence that we observed is itself related to fluctuations of activity in attentional control networks. Activity in frontal regions has also been linked to subjective awareness reports, independent of performance (Lau & Passingham, 2006; Persaud et al, 2011; Rounis, Maniscalco, Rothwell, Passingham, & Lau, 2010), and although alpha oscillations are thought to reflect visual cortex excitability (Romei, Brodbeck, et al, 2008; Samaha, Gosseries, et al, 2016), thereby acting on perceptual inputs, it is possible that confidence is ultimately computed from the read out of sensory signals by higher order regions (Rahnev, Koizumi, McCurdy, D’Esposito, & Lau, 2015). …”
Section: Discussionmentioning
confidence: 99%